2004
DOI: 10.1016/j.ijid.2003.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic valve endocarditis due to Listeria monocytogenes

Abstract: Despite problems associated with microbial persistence and relapses in other forms of human listeriosis, antimicrobial therapy alone may be a successful treatment for listerial endocarditis, including cases occurring on prosthetic valves. Valve replacement may be reserved for complicated cases with valve dehiscense, cardiac failure or myocardial abscess. Overall mortality was 35.3%, although most patients who died did so before 1985 and since then mortality has been significantly reduced to 12%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 52 publications
2
26
0
2
Order By: Relevance
“…Endocarditis is uncommon (only documented in approximately 80 cases), and has been reported in immunocompromised and competent hosts [1, 3]. Prosthetic valve endocarditis (PVE) and cardiac device infections caused by L. monocytogenes are rare [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Endocarditis is uncommon (only documented in approximately 80 cases), and has been reported in immunocompromised and competent hosts [1, 3]. Prosthetic valve endocarditis (PVE) and cardiac device infections caused by L. monocytogenes are rare [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Listeria endocarditis is a rare condition which can affect native valves, prosthetic valves [4, 5], or nonvalvular intracardiac devices [6]. A review of 68 patients with listeria endocarditis from 1955 to 2000 showed that most patients were immunosuppressed and did not have a documented exposure to contaminated food.…”
Section: Discussionmentioning
confidence: 99%
“…A review of 68 patients with listeria endocarditis from 1955 to 2000 showed that most patients were immunosuppressed and did not have a documented exposure to contaminated food. Patients with native valve endocarditis had a higher mortality rate compared to those with prosthetic valve endocarditis [5]. …”
Section: Discussionmentioning
confidence: 99%
“…Mortality rates are high, particularly among the immune suppressed, and residual disability is common among survivors 5 7 8. Other rare manifestations of Listeria infection include endocarditis and localised infections as a consequence of bacteraemia 9 10. In pregnancy, uncomplicated bacteraemia is the most common syndrome encountered, although chorioamnionitis, placental infection and infection of the fetus may occur 1…”
Section: Discussionmentioning
confidence: 99%